MosaicHunter: accurate detection of postzygotic single-nucleotide mosaicism through next-generation sequencing of unpaired, trio, and paired samples - Huang, August Yue; Zhang, Zheng; Ye, Adam Yongxin; Dou, Yanmei; Yan, Linlin; Yang, Xiaoxu; Zhang, Yuehua; Wei, Liping (Nucleic acids research, 2017)
Genomic mosaicism arising from postzygotic mutations has long been associated with cancer and more recently with non-cancer diseases. It has also been detected in healthy individuals including healthy parents of children affected with genetic disorders, highlighting its critical role in the origin of genetic mutations. However, most existing software for the genome-wide identification of single-nucleotide mosaicisms (SNMs) requires a paired control tissue obtained from the same individual which is often unavailable for non-cancer individuals and sometimes missing in cancer studies. Here, we present MosaicHunter (http://mosaichunter.cbi.pku.edu.cn), a bioinformatics tool that can identify SNMs in whole-genome and whole-exome sequencing data of unpaired samples without matched controls using Bayesian genotypers. We evaluate the accuracy of MosaicHunter on both simulated and real data and demonstrate that it has improved performance compared with other somatic mutation callers. We further demonstrate that incorporating sequencing data of the parents can be an effective approach to significantly improve the accuracy of detecting SNMs in an individual when a matched control sample is unavailable. Finally, MosaicHunter also has a paired mode that can take advantage of matched control samples when available, making it a useful tool for detecting SNMs in both non-cancer and cancer studies.